Analysis of Mini Longline Fishing Rate Using Hook Sizes 5 and 7 and Mini Longline Feasibility effort in The Waters of Pambang’s Gulf Bantan District Bengkalis Regency Riau Province - Tarmizi '; Arthur Brown; Pareng Rengi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was conducted on March 31 until 4 April 2014, which took place in the waters of thePambang’s Gulf Bantan District Bengkalis regency Riau province. The metode used in this study isexperimental and survey methods with case studies, namely by direct observation to look the variouslongline fishing activities.The pupose of this studi is to analyze of the catch rate with effectiveness of different sizes oflongline hooks, showing fish catches by different hook sizes, analyze the feasibility of longline effort. Theresults of this research can be an information for researchers, especially for the waters of Pambang’s Gulfon longline gear and longline feasibility effort.The results of this research show that hook rate measuring value of the hooks 7a: 11.1, 5a: 8.9, 7b:10.7, and 5b: 7.6. Based on statistic test One Way ANOVA (Analisysisi of Variance) obtained sig. 0.805 isgreater than the value of α = 0.05 level (p-value> α), its means that there is no difference in fish hook rateby hook. The results of the feasibility calculations for some criteria indicate that longline fishing effortworth forwarded, it can be seen from the value of BCR (Benefit Cost Ratio) of 1.013, FRR value(FinancialRate of Return) by 2.823%, PPC Value (Payback PeriodofCapital) of 35.422 years.Keywords : mini longline, analyze, effort feasibility, Pambang’s gulf